2006
DOI: 10.1097/01.hjh.0000249701.49854.21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between low-grade inflammation and arterial stiffness in patients with essential hypertension

Abstract: In hypertensive individuals, hsCRP is related to PWV, a direct marker of arterial stiffness, but not to AIx, a measure of wave reflections. Whether inflammation might act as a pathogenetic or modulating factor in arterial stiffening in chronic hypertension has to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 50 publications
3
53
0
8
Order By: Relevance
“…Several cross-sectional clinical studies demonstrated significant associations of markers of systemic inflammation, such as CRP, with pulse wave velocity. 20,21 In a recent study, Zheng et al 22 evaluated data from a community-based, prospective, long-term follow-up observational study, the Asymptomatic Polyvascular Abnormalities Community study. Of 4025 patients followed up for an average of 27 months, 432 patients developed incident hypertension.…”
Section: Inflammation and Hypertensionmentioning
confidence: 99%
“…Several cross-sectional clinical studies demonstrated significant associations of markers of systemic inflammation, such as CRP, with pulse wave velocity. 20,21 In a recent study, Zheng et al 22 evaluated data from a community-based, prospective, long-term follow-up observational study, the Asymptomatic Polyvascular Abnormalities Community study. Of 4025 patients followed up for an average of 27 months, 432 patients developed incident hypertension.…”
Section: Inflammation and Hypertensionmentioning
confidence: 99%
“…The ensuing arterial stiffness is an independent cardiovascular risk factor. 73 From this perspective, it can be deduced that hypertension is an independent risk factor for coronary heart disease and vasculogenic erectile dysfunction. In the work of Modebe 74 in Nigeria, 8% of the untreated hypertension population had erectile dysfunction while this was 61% in the treated group.…”
Section: Hypertensionmentioning
confidence: 99%
“…4,7 Traditional risk factors for atherosclerosis, such as smoking, hypercholesterolaemia, hypertension, diabetes and a sedentary lifestyle may be common or indeed more common in RA than in the population as a whole, but do not account for all of the increase in circulatory disease. There is now a large body of evidence 8 that the chronic inflammatory state can enhance the deleterious effects of some traditional risk factors, such as the association between systemic inflammation and arterial wall stiffness in hypertension, 9 or the proatherogenic lipid profile (high LDL and lipoprotein(a), low HDL) seen with increasing rheumatoid disease activity, 10 as well as introducing some new ones. The burden of addressing IHD in RA is therefore divided between rigorous control of traditional risk factors, and effective disease control through immunosuppression.…”
Section: Cardiovascular Disease In Rheumatoid Arthritismentioning
confidence: 99%